A Study on The Impact of Economic Development and Environmental Pollution Relationship in Jiangsu Province - Zhang, Rui (Transactions on Environment, Energy and Earth Sciences, 2024)
This paper selects per capita GDP of Jiangsu Province from 2000 to 2020 as the indicator of economic development, and uses chemical oxygen demand (COD) emissions, sulfur dioxide (SO2) emissions, general industrial solid waste generation, and hazardous waste generation as indicators of environmental pollution. Based on the theoretical foundation of the Environmental Kuznets Curve (EKC), the paper conducts an empirical analysis of the relationship between economic development and environmental pollution using Eviews software. The results show that:(1) The EKC for SO2 emissions fits an inverted N-shaped curve and has surpassed the second inflection point of this curve.(2) The EKC for general industrial solid waste generation fits an inverted U-shaped curve and has not yet reached its inflection point.(3) The EKC for hazardous waste generation fits a U-shaped curve and has surpassed the inflection point of this curve.